The Efficacy of Culturally Responsive Pedagogy for Low-Proficiency International Students in Online Teaching and Learning - Khoo, Elaine; Huo, Xiangying (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2022)
International students with low academic English proficiency face challenges with reading their course materials and writing assignments. Their challenges are exacerbated during remote learning, as they remain in their home countries, immersed in their home languages, which may be quite distant from academic English. To investigate the effects of culturally responsive pedagogy for international students online, quantitative and qualitative data were collected from a learner-driven, instructor-facilitated (LeD-InF) support program at a large university in southern Ontario. This fully online delivery of the Reading and Writing Excellence (RWE) program was re-envisioned from a long-running co-curricular program that addressed students’ academic English reading, writing, and critical thinking needs. Among eight groups (with the total enrolment of 154) in the Fall 2020 academic term cycle and nine groups (with the total enrolment of 226) in the Winter 2021 academic term cycle of the online RWE program, the intervention groups that were additionally supported with culturally responsive pedagogy had the highest volume of writing output and engagement metrics among all groups. The text data (of student voices and experiences) also reinforces the efficacy of culturally responsive pedagogy in facilitating student experience, constructing identities, promoting learner agency, increasing satisfaction, improving students’ perceptions of learning, and realizing transformative inclusivity.